Faktor Penghambat Kembali Bekerja pada Pasien Gangguan Mental Umum - Cahyani, Eliza; Daulima, Novy Helena Catharina; Hargiana, Giur (Journal of Telenursing (JOTING), 2024)
This research aims to analyze the factors that prevent individuals who experience mental disorders in general from being able to return to work. The method used is a systematic review by searching for articles tailored to formulating research questions with PEO formulations in seven databases: Scopus, ScienceDirect, Pubmed, Proquest, Sage Journals, Oxford, Taylor & Francis. The research found two categories: internal factors, job status, workability, positive attitude, symptom severity, self-efficacy, and male. In contrast, external factors were supervisor support, loss of work contract, initial unemployment, low control over work, job tension, inflexible working hours, and no possibility of working from home. In conclusion, recovery can be achieved if internal and external factors work together and contribute positively to the client. Keywords: Inhibiting Factors, Common Mental Disorders, Return to Work